Analysis Of The Need To Apply Contextual Learning Principles In Digital Fotonovela - Damayanti, Ida; Siregar, Evelyn; Solihatin, Etin; Wirasti, RA Murti Kusuma; Lestari, Ika (UNIVERSITAS PAKUAN, 2020)
Pancasila and Citizenship Education learning aims to achieve civic character (civic disposition), civic skills and civic knowledge . The material studied is related to the 1945 Constitution, Pancasila, the Unitary State of the Republic of Indonesia and Bhinneka Tunggal Ika. The material provided teaches many concepts, but to achieve character or attitude, it is necessary to develop learning media that accommodates the material, Civics learning objectives and students who are the millennial generation with their own characteristics. The aim of this research is to analyze the needs of digital Fotonovelas with analysis stages: needs analysis, analysis of digital Fotonovela characteristics, and curriculum analysis so that information can be obtained about the initial conceptual design of digital Fotonovelas using contextual learning principles. The research method uses mixed methods , qualitative and literature study. Data collection techniques were carried out using observation, interviews with educators and students and literature reviews . The data obtained was analyzed using qualitative data analysis techniques. The data analysis process uses the Miles and Huberman interactive analysis model which includes 4 stages, namely data collection, data reduction, data presentation and drawing conclusions